Path Navigation using Bluetooth Low Energy-Beacon (International Journal of Advanced Research in Computer Science, 2017)
Beacons turn the physical world into a new digital channel. They bring digital content and engagement closer to the point of purchase. Beacon technology transmits small packets of data using Bluetooth Low Energy. When a customerâ€™s phone â€œhearsâ€ the beacon it knows how close it is and we can then send a message, a notice, a piece of media or other information. Beacons are low-power transmitters equipped with Bluetooth Low Energy or BLE. Bluetooth Low Energy help mobile devices to detect Proximity and determine micro-location. Advantages of Bluetooth low energy devices are it works up to 100 meters, doesnâ€™t drain the phone battery.In this paper problems with beacon are described and path navigation using Bluetooth Low Keywords: Beacon , Internet of Things â€“ Beacons The New Revolution, Bluetooth Low Energy, Path Navigation, Background Monitoring, Ranging Beacons, Proximity, Tracking